Pengaruh Keluarga dan Kelompok Referensi Terhadap Keputusan Konsumen Membeli Kosmetika Khusus Pria (Studi Kasus Merek Nivea Men di Kota Pekanbaru) - Syifa, Silvia; Sulistyowati, Lilis; Musfar, Tengku Firli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to testing the influence of family and reference group which contains of friendship group, work group, shopping group, consumer-action group, and netizen toward consumer decision on purchasing The Nivea Men Brand in Pekanbaru. The sample of this research are Nivea Men consumers, they are teenager men in Pekanbaru. Sample of this research only consumers that using Garnier Men who purchasing the products with their own money (not present or gift), and consumers that considered mature enough to fill up the questioner (more than 17 years old). Data analysis using SPSS 20 with multiple linear regressions method. The results indicate that not all variable significantly influence on consumer decision to purchase Nivea Men brand in Pekanbaru. Only friendship group variable and consumer-action group variable have significant influence on consumer decision to purchase men’s cosmetic from Nivea Men brand in Pekanbaru.Keywords: family, friendship group, work group, shopping group, consumer-action group, netizen, and consumer purchasing decision.